Education on the effectiveness of sugar-based mosquito traps in controlling dengue fever vectors - Jenvia Rista Pratiwi; Fadila Fitria Wulandari; Isma Dewanti Aprilya; Irani Salsabila (University of Merdeka Malang, 2025)
Dengue hemorrhagic fever (DHF) is a serious health problem in Indonesia with the Aedes aegypti mosquito as the main vector. This study aims to evaluate the effectiveness of sugar solution-based mosquito traps in reducing mosquito populations at SD Ummu Aiman. The traps were made using simple materials and then distributed to the school's mosquito-prone areas. Socialization and education were conducted for teachers through presentations, questions and answers, and hands-on practice of making the traps. Their effectiveness was evaluated through an online questionnaire. The results showed a significant reduction in the frequency of mosquito presence after trap installation, with an increase in respondents who no longer encountered mosquitoes from 5 percent to 25 percent. 85 percent of respondents considered the traps effective and safe, and the majority were willing to implement them in their area. The program successfully increased teachers' knowledge and engagement in mosquito control, despite facing constraints such as limited time, resources, and odor from the traps. Continuous support and regular evaluation are expected to increase the effectiveness and acceptance of this innovation. The sugar solution-based mosquito trap innovation is expected to be an environmentally friendly and sustainable solution for dengue vector control in schools.